Effect of ezetimibe on low- and high-density lipoprotein subclasses in sitosterolemia. (May 2017) - Othman, Rgia A.; Myrie, Semone B.; Mymin, David; Roullet, Jean-Baptiste; Steiner, Robert D.; Jones, Peter J.H.
Abstract: Background and aims: Sitosterolemia displays high plasma total sterols [high plant sterols (PS) + normal to high total cholesterol (TC)] with normal to moderately elevated low-density lipoprotein (LDL) levels. High LDL, intermediate-density lipoprotein (IDL) and very low-density lipoprotein (VLDL) particles, low high-density lipoprotein (HDL), and increased non-HDL and the ratios of TC and triglycerides (TG) to HDL can increase the risk for atherosclerosis. Ezetimibe (EZE) can reduce plasma PS and TC levels in sitosterolemia, but its effect on lipoprotein subclasses has not been previously reported. Methods: Sitosterolemia patients (n = 8) were taken off EZE for 14 weeks (OFF EZE) and placed on EZE (10 mg/d) for 14 weeks (ON EZE). Serum lipids were measured enzymatically and lipoprotein subclasses were assessed by polyacrylamide gel electrophoresis. Results: EZE reduced ( p  < 0.05) total sterols (−12.5 ± 4.1%) and LDL-sterol (−22.7 ± 5.7%) and its sterol mass of large VLDL (−24.4 ± 4.5%), VLDL remnants (−21.1 ± 7.9%) and large IDL (−22.4 ± 7.2%) compared to OFF EZE. EZE did not affect large LDL subclasses or mean LDL particle size (273.8 ± 0.6 vs. 274.6 ± 0.3 Å). EZE increased HDL-sterol (25.5 ± 8.0%, p  = 0.008) including intermediate (34 ± 14%, p  = 0.02) and large (33 ± 16%, p  = 0.06) HDL. EZE reduced non-HDL-sterol (−21.8± 5.0%), total sterols/HDL (−28.2 ± 5.5%) and TG/HDL (−27.4 ± 6.5%, all p  < 0.01). Conclusions: EZE improves VLDL and HDL subfraction distribution, thereby reducing the atherogenic lipid profile, thus providing potential clinical benefit in sitosterolemia beyond TC and PS reduction. Highlights: Ezetimibe (EZE) improves serum sterols and lipoprotein levels in sitosterolemia. VLDL, IDL, and medium and large HDL subclasses increased with EZE. EZE had no impact on LDL subclasses and particle size in sitosterolemia.